Acute kidney injury in patients with severe rash on vemurafenib treatment for metastatic melanomas. (10th October 2013) - Regnier‐Rosencher, E.; Lazareth, H.; Gressier, L.; Avril, M.F.; Thervet, E.; Dupin, N.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Vemurafenib, a selective BRAF (v‐raf murine sarcoma viral oncogene homologue B1) inhibitor is used to treat metastatic melanoma in patients with BRAF mutations. It has significant dermatological adverse effects, but acute kidney injury (AKI) has never before been reported in treated patients. What does this study add? We report a cluster of four cases of AKI associated with severe grade 3 (Common Terminology Criteria for Adverse Events) cutaneous drug reactions related to vemurafenib. Vemurafenib was reintroduced at a lower dose, without a relapse of the rash, but renal function deteriorated again. This association with a rapid major or complete response raises numerous questions.